Sentencing outcomes of black, Hispanic, and white males convicted under federal sentencing guidelines - Hebert, Christopher G. (Criminal justice review, 1997)
Although the issue of racial disparities (black vs. white) in sentencing outcomes has received considerable research attention, comparatively little research has considered the question of ethnic disparity (Hispanic vs. white). To fill that void, this study uses calendar year 1989 data collected and distributed by the United States Sentencing Commission to examine the sentence outcomes of Hispanic and black offenders compared to white offenders convicted of violating federal drug laws. After controlling for legally relevant factors, socioeconomic factors, and legal contextual factors, it was found that blacks convicted of cocaine offenses and Hispanics convicted of cocaine and marijuana offenses were sentenced more harshly than white offenders